Anaerobic co-digestion of cow manure, food waste and waste activated sludge with Trametes versicolor pre-treatment under mesophilic condition - Uzun, Ömer. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2019., 2019)
Biological pre-treatment with fungal species such as Trametes versicolor using their extracellular enzymes leads to an improvement in biodegradation of lignocellulosic substrates and increases biogas production. In this study, cow manure (M), food waste (F) and waste activated sludge (W) were co-digested under mesophilic conditions with and without pre-treatment with T. versicolor captured in Ca-alginate beads. T. versicolor was incubated in the medium for 10 days and then it was encapsulated in Ca-alginate beads, and the pre-treatment process was conducted for the combination of substrates of MF, MW, FW and FMW. Following the biological pre-treatment, same amount of volatile solids-containing feedstock mixtures were inoculated with anaerobic seed sludge with an inoculum to substrate ratio of 2:1 (VS basis) and anaerobic co-digesters were set up. The results indicated that pre-treatment with T. versicolor led to an increase in methane yield for the combination of MF, MW, FW and FMW by 35%, 8%, 16% and 23%, respectively. Besides, the results showed that the food waste was the most significant substrate for improving methane yield. Moreover, volatile fatty acid concentrations in the digesters were at their highest level on the 3rd day of their operation and also significantly lower in the digesters that did not include food waste. These results can also be interpreted that the acidogenic phase was successfully accomplished within the first three days; the food waste led to the acceleration of the acidification stage.
Keywords: Sewage -- Purification -- Anaerobic treatment.; Trametes versicolor.; Cattle -- Manure -- Recycling.; Food waste -- Recycling.; Sewage sludge precipitants -- Recycling.